Therapies to decrease tooth whitening sensitivity - Achachao Almerco, Kelly (2019)
The most common side eﬀect in tooth bleaching is tooth sensitivity because of the pulp reaction to free radicals produced by the hydrogen peroxide used in bleaching products. Diﬀerent therapies have been used before, during and after to reduce tooth sensitivity, agents that block nerve repolarization such as potassium nitrate and agents that block dentinal tubules: amorphous calcium phosphate, calcium sodium phosilicate, calcium gluconate, hydroxyapatite, GLUMA and fluor; alternative therapies such as the use of anti-inflammatory, antioxidants and laser application which have also been mentioned in the literature. The aim of this review is to show the scientific evidence on the diﬀerent methods to decrease the sensitivity on tooth bleaching.